Visualisation and Interpretation of Moraine Landscapes in North- East Germany – the Ideal View on Landscape - Dalchow, Claus; Kiesel, Joachim; Lutze, Gerd (DIE ERDE – Journal of the Geographical Society of Berlin, 2012)
<div style="font-size: 12px; font-family: serif; left: 657.479px; top: 623.862px; transform: scale(0.999, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-font-name="g_font_p0_2" data-canvas-width="3.9960000000000004">Visual representations of the earth’s surface can nowadays be produced on the basis of data with high resolution and accuracy. Especially 3D-visualisations can provide an excellent basis for “comprehensive cognition”. However, specific accentuations and generalisations are necessary to turn them into an adequate cognitive tool. Here we introduce a specific generalisation approach, presented by visualisations of two lowland landscape sections in the state of Brandenburg, Germany.